Facilitation of axonal transcriptome analysis with quantitative microfluidic devices. Issue 9 (17th April 2023) - Yang, Zhuoxuan; Yu, Jun; Zhang, Jian; Song, Huixue; Ye, Haixia; Liu, Jianhui; Wang, Nijia; Che, Pengfei; Long, Gaoxin; Wang, Yunxuan; Park, Jaewon; Ji, Sheng-Jian
Abstract : Two newly developed quantitative chambers, multi-compartmental quantitative bipartite chamber (MQBC) and long quantitative tripartite chamber (LQTC), could dramatically increase the efficiency in collecting axonal RNA. Abstract : Microfluidic chambers are powerful tools for studying axonal mRNA localization and translation in neurons. In addition to specific manipulation and measurements of axons, microfluidic chambers are used for collecting axonal materials to perform axonal transcriptome analysis. However, traditional bipartite and tripartite chambers have limitations either in purity or quantity of collected axons. Here, we improved the design of traditional chambers. Moreover, we developed two new quantitative chambers, multi-compartmental quantitative bipartite chamber (MQBC) and long quantitative tripartite chamber (LQTC). Compared with the traditional chambers, MQBC and LQTC could dramatically increase the efficiency in collecting axonal RNA. Finally, we applied these chambers to do comparative axon transcriptome analysis of different types of neurons. Thus, our newly designed quantitative chambers significantly improve axon collection efficiency and facilitate axonal transcriptome analysis.